2017
DOI: 10.1007/s10461-017-1891-6
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of a Structural Intervention to Address Alcohol Use Among Gay Bar Patrons in San Francisco: The PACE Study

Abstract: We evaluated the impact on alcohol intake and blood alcohol concentration (BAC) of a multi-level structural intervention to increase the availability of free water, coupled with messaging on pacing alcohol intake and normative feedback of blood alcohol concentration in a convenience sample of gay bars in San Francisco. Participants (n = 1,293) were recruited among exiting patrons of four gay bars (two intervention bars and two control bars). Participants were surveyed on alcohol intake and BAC was measured by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(36 citation statements)
references
References 45 publications
1
32
0
3
Order By: Relevance
“…Structural interventions aim to change the environments in which risk behavior occurs, such as limiting alcohol availability. Although no systematic reviews exist to date to assess their effect on alcohol consumption, an increasing number of intervention trials have demonstrated success in structural approaches at reducing alcohol consumption and related problems in diverse populations and contexts [17].…”
Section: Introductionmentioning
confidence: 99%
“…Structural interventions aim to change the environments in which risk behavior occurs, such as limiting alcohol availability. Although no systematic reviews exist to date to assess their effect on alcohol consumption, an increasing number of intervention trials have demonstrated success in structural approaches at reducing alcohol consumption and related problems in diverse populations and contexts [17].…”
Section: Introductionmentioning
confidence: 99%
“…Potential policies might emulate those in Australia, where free water availability is mandated in settings serving alcohol (http://www.rgl.wa.gov.au/docs/default-source/rgl/drinking_water.pdf?sfvrsn=0). In our parent study, the provision of free water coupled with a media campaign on pacing alcohol intake with water was significantly associated with a reduction in BAC and self-reported binge drinking among exiting gay bar patrons in San Francisco (Charlebois et al, 2017).…”
Section: Discussionmentioning
confidence: 85%
“…This qualitative study was part of a larger study in which we recruited four bars (two intervention bars and two control bars) to assess whether harm reduction messaging highlighting pacing alcohol consumption, increased access to free water, and normative feedback about alcohol intake would reduce blood alcohol concentration (BAC), binge drinking, and sexual HIV risk of bar patrons (Charlebois et al, 2017). This current study reported here focuses on bar patrons’ management strategies and how those strategies intersect with environmental factors that affect their ability to successfully implement those strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies over the past decades suggest that MSM are likely to frequent bars and other social events such as house parties for socialization and meeting new sexual partners, suggesting a strong need for interventions to reduce alcohol consumption among MSM (Charlebois, Plenty, Lin, Ayala, & Hecht, 2017). This is especially necessary because a proliferation of studies have observed the strong link between alcohol consumption and unsafe sexual behavior.…”
Section: Are Virtual Interactions and Choices Predictive Of Real-lifementioning
confidence: 99%
“…Bruce, Kahana, Harper, Fernández, & ATN, 2013; Colfax et al, 2004; Gerbi, Habtemariam, Tameru, Nganwa, & Robnett, 2009; Santos, Jin, & Raymond, 2015). While extant interventions targeting alcohol consumption and its link to risky sexual behavior showed that altering the social environment (i.e., making the choice of water available in gay bars) could reduce alcohol intake (Charlebois et al, 2017), such interventions are still costly in terms of both time and effort. Such interventions must rely on (1) constantly providing messages that remind MSM of the availability and their desired choice of water, and (2) successfully negotiating with social venues (e.g., gay bars) to offer such messages.…”
Section: Are Virtual Interactions and Choices Predictive Of Real-lifementioning
confidence: 99%